Analysis of Stakeholders Involvement in the Implementation of the M.A. Literature Curriculum at Kabale University Using E-Learning Approach - Ocan, Johnson; Tukwasibwe, Constance; Oketch, Chrysostom (East African Journal of Education Studies, 2021)
The purpose of the study was to report on an empirical study of the involvement of stakeholders in the implementation of the MA Literature Curriculum at Kabale University using e-Learning approach. The study used a mixed method approach of both qualitative and quantitative techniques. In this study, curriculum stakeholders were found to significantly influence curriculum development, hence collaboration with these stakeholders through feedback, critique and advice can only serve to meld the content and method of delivery of the curriculum. This study extends the application of a modified curriculum development process model based on ADDIE (analysis, design, development implementation and evaluation). It recognizes the different stakeholders and their input for curriculum innovation. Therefore, identifying, understanding and managing stakeholders’ involvement in curriculum implementation is a key driver in the curriculum development. This paper is not concerned with comparing and exploring possible techniques of identifying university stakeholders with the aim of choosing the most suitable one, but it is intended to clarify on the categorization of the internal and external stakeholders